The influence of professional status on maximal and rapid isometric torque characteristics in elite soccer referees - Palmer, T. B.; Hawkey, M. J.; Smith, D. B.; Thompson, B. J. (The Journal of Strength and Conditioning Research, 2014)
The purpose of this study was to examine the effectiveness of maximal and rapid isometric torque characteristics of the posterior muscles of the hip and thigh and lower-body power to discriminate between professional status in full-time and part-time professional soccer referees. Seven full-time (mean ± SE: age = 36 ± 2 years; mass = 82 ± 4 kg; and height = 179 ± 3 cm) and 9 part-time (age = 34 ± 2 years; mass = 84 ± 2 kg; and height = 181 ± 2 cm) professional soccer referees performed 2 isometric maximal voluntary contractions (MVCs) of the posterior muscles of the hip and thigh. Peak torque (PT) and absolute and relative rate of torque development (RTD) were calculated from a torque-time curve that was recorded during each MVC. Lower-body power output was assessed through a vertical jump test. Results indicated that the rapid torque characteristics were greater in the full-time compared with the part-time referees for absolute RTD (p = 0.011) and relative RTD at 1/2 (p = 0.022) and 2/3 (p = 0.033) of the normalized torque-time curve. However, no differences were observed for PT (p = 0.660) or peak power (Pmax, p = 0.149) between groups. These findings suggest that rapid torque characteristics of the posterior muscles of the hip and thigh may be sensitive and effective measures for discriminating between full-time and part-time professional soccer referees. Strength and conditioning coaches may use these findings to help identify professional soccer referees with high explosive strength-related capacities and possibly overall refereeing ability.